Loss of function of PCDH12 underlies recessive microcephaly mimicking intrauterine infection. (24th May 2016) - Aran, Adi; Rosenfeld, Nuphar; Jaron, Ranit; Renbaum, Paul; Zuckerman, Shachar; Fridman, Hila; Zeligson, Sharon; Segel, Reeval; Kohn, Yoav; Kamal, Lara; Kanaan, Moien; Segev, Yoram; et al.
Abstract : Objective: To identify the genetic basis of a recessive syndrome characterized by prenatal hyperechogenic brain foci, congenital microcephaly, hypothalamic midbrain dysplasia, epilepsy, and profound global developmental disability. Methods: Identification of the responsible gene by whole exome sequencing and homozygosity mapping. Results: Ten patients from 4 consanguineous Palestinian families manifested in utero with hyperechogenic brain foci, microcephaly, and intrauterine growth retardation. Postnatally, patients had progressive severe microcephaly, neonatal seizures, and virtually no developmental milestones. Brain imaging revealed dysplastic elongated masses in the midbrain–hypothalamus–optic tract area. Whole exome sequencing of one affected child revealed only PCDH12 c.2515C>T, p.R839X, to be homozygous in the proband and to cosegregate with the condition in her family. The allele frequency of PCDH12 p.R839X is <0.00001 worldwide. Genotyping PCDH12 p.R839X in 3 other families with affected children yielded perfect cosegregation with the phenotype (probability by chance is 2.0 × 10 −12 ). Homozygosity mapping revealed that PCDH12 p.R839X lies in the largest homozygous region (11.7 MB) shared by all affected patients. The mutation reduces transcript expression by 84% ( p < 2.4 × 10 −13 ). PCDH12 is a vascular endothelial protocadherin that promotes cellular adhesion. Endothelial adhesion disruptions due to mutations in OCLN or JAM3 also cause congenital microcephaly, intracranial calcifications, and profound psychomotor disability. Conclusions: Loss of function of PCDH12 leads to recessive congenital microcephaly with profound developmental disability. The phenotype resembles Aicardi-Goutières syndrome and in utero infections. In cases with similar manifestations but no evidence of infection, our results suggest consideration of an additional, albeit rare, cause of congenital microcephaly.